Association between mixed exposure of non-persistent pesticides and liver fibrosis in the general US population: NHANES 2013–2016 - Shuge Shu; Yuan Li; Xiangyu Yu; Xinting Chen; Ummara Abdullah; Yongquan Yu (Ecotoxicology and Environmental Safety)
People are continually and simultaneously exposed to various non-persistent pesticides as these chemicals are ubiquitously distributed in the environment. Toxicological studies have indicated the associations between non-persistent pesticides and liver fibrosis in vitro and in vivo. However, epidemical study on the deleterious effect of non-persistent pesticides on the risk of liver fibrosis is rather limited. To examine the relationship between mixed non-persistent pesticides exposure and liver fibrosis, and to identify the potential pesticides of significant importance, this study enrolled the representative individuals from the NHANES 2013–2016 survey cycles, in which urinary non-persistent pesticides were measured. Liver fibrosis was determined based on the alternative noninvasive tests Fibrosis-4 index (FIB-4) and Hepamet Fibrosis Score (HFS). Survey-weighted linear/logistic regression and Bayesian kernel machine regression (BKMR) were used to detected the independent and combined associations between non-persistent pesticides and liver fibrosis, respectively. In single exposure analysis, significant and persistent associations were identified for 3,5,6-trichloropyridinol (TCPY), para-nitrophenol (PNP), glyphosate (GLYP) and 2,4-dichlorophenoxyacetic acid (2,4-D) exposure with both continuous and dichotomous liver fibrosis outcomes. Of them, TCPY and GLYP had the highest effect estimates, with the corresponding FIB-4 coefficient (β) being 0.09 (0.05–0.13, model 3) and 0.09 (0.06–0.12, model 3), respectively. In BKMR analysis, positive associations between pesticides mixture and FIB-4 and HFS liver fibrosis were identified. The results of Posterior Inclusion Probability (PIP) further showed that GLYP, TCPY, and PNP were the main contributors to the overall effects of pesticides mixture, and the corresponding PIPs were 1.000 (1.000), 1.000 (0.914) and 0.972 (0.819) for FIB-4 (HFS) liver fibrosis, respectively. This study indicates that exposure to non-persistent pesticides mixture is associated with increased risk of liver fibrosis in humans, and provide new insight into the hepatotoxic potential of non-persistent pesticides.